Controlling political communication in the blogosphere: Business as usual in Malaysia - Shuaib, Farid Sufian (2010)
Malaysia has a list of restrictive laws that prevent publication of political communication. Most of these laws were enacted before the explosion of online communication through online news portal and blogs. Malaysia, her citizen and her government, have embraced this information communication technology on the belief of its ability to propel the nation to become a developed nation. Because of this belief, contrary to provisions of the restrictive laws, the government guarantee no censorship in the internet. This guarantee invited expectation that restrictive laws that have been applied to the press and broadcasters will not be applied in online communication. The objective of this paper is to examine whether this expectation materialised. This paper examines to what extent the guarantee assist in liberalisation of political communication through online publication. Legal provisions, case reports and incidents will be analysed in this study.